ANALISIS KONSUMSI BERAS PADATINGKAT RUMAH TANGGA DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Cristovao R; Slamet Hartono; Jangkung Handoyo Mulyo (Agro Ekonomi, 2007)
The objectives of the study were (1) to determine thefactors influencing rice consumption in urban and rural areas of Yogyakarta Special Province and (2) to determine the own price, cross price and income elasticity of rice consumption at different income levels in rural and urban areas. National Socio-Economic Survey (SUSENAS) data of 2005 Yogyakarta Special Province on rice consumption was used Totalrespondents 1990 households. Regression model used in the analysis was OLS. The result showed that thefactors that influence the consumption of rice are the price of the rice itself, price of the related household goods, income level, education of the mother, number offamily members, and location. Thefactors that individually influence rice consumption vary by kinds of rice, location, and income level. Therefore, the demand of rice in DIY is inelastic, the change of price did not significantly influence rice demand. Generally, rice is normal good at low income household level in the rural and urban areas andfor middle income in the rural, and in middle income and high income in the urban, rice is a inferior good. In other side, rice is Substituted for cassava and sweet potato. Rice is complementary for catfish, fermented soybean cake, cassava, egg, and tofu.Keywords: rice consumption, elasticity, substitution, complementary.